Application of the Lambert W function for the impact of the exhaust gas turbocharger on nanoscale PM emissions from a TGDI engine. (25th April 2016) - Cucchi, Matteo; Samuel, Stephen
Highlights: Nano-scale PM from a TGDI engine is measured before and after the turbine. Variations in PM across the turbine are modelled by means of the Lambert W Function. The model predicts turbine-out PM with a coefficient of determination of 0.917. The input variables of the model are known to the ECU or can be measured on-board. The model could be implemented within engine performance simulation software. Abstract: A phenomenological model based on the Lambert W Function is presented which is capable of describing the variations in nano-scale particulate matter (PM) number concentrations across the turbine stage of a turbocharged gasoline direct injected (TGDI) engine over a wide range of engine operating conditions with a coefficient of determination ( C D ) of 0.917. The model predictors are variables which are available to the engine control unit (ECU) either by means of stored maps or on-board measurements. The suitability of the proposed model for real-time usage within the ECU for vehicle calibration is discussed.